RNA-protein interactions in the nuclei of Xenopus oocytes: complex formation and processing activity on the regulatory intron of ribosomal protein gene L1. - Santoro, B (1994)
The gene encoding ribosomal protein L1 in Xenopus laevis is known to be posttranscriptionally regulated; the third intron can be processed from the pre-mRNA in two alternative ways, resulting either in the production of L1 mRNA or in the release of a small nucleolar RNA (U16). The formation of splicing complexes was studied in vivo by oocyte microinjection. We show that spliceosome assembly is impaired on the L1 third intron and that the low efficiency of the process is due to the presence of suboptimal consensus sequences. An analysis of heterogeneous nuclear ribonucleoprotein (hnRNP) distribution was also performed, revealing a distinct site for hnRNP C binding proximal to the 5' end of the L1 third intron. Cleavage, leading to the production of the small nucleolar RNA U16, occurs in the same position, and we show that conditions under which hnRNP C binding is reduced result in an increase of the processing activity of the intron.